Sufism and its Relationship with the Development of Human Potential - Khairul Nizam Bin Zainal Badri (Jurnal Ilmiah Iqra', 2021)
Sufism and its Relationship with the Development of Human Potential. Research paper: Sufi thought is, in fact, an active mind because humans are seen as potential beings with high levels of consciousness. In the Sufi definition, the consciousness of mysticism is an active consciousness that leads to the introduction of God. This qualitatively conducted survey found that the introduction of God in a Sufi perspective will lead to the development of potential. Using a literature approach, this study also makes a comparison with Western views on the development of human potential. This introduction of God will further cultivate a love for God that will bring forth the knowledge of the development of human potential. This knowledge is a gift of God because, with this knowledge, man develops his potentials and then translates them into creativity, sharpness of mind, and optimism in life by God's truth